Analysis of a heat pump with solid desiccant tube bank - Kiatsiriroat T. (2014)
In this paper, the analysis of silica gel formed in a staggered tube bank arrangement for the reduction of energy consumption in a heat pump dehumidifier is presented. The mathematical models for the desiccant and the heat pump have been developed. The simulated results agree quite well with those of the experiments. The desiccant could reduce the heat pump load by about 7-20 per cent at the inlet air conditions of about 30-50°C and 70-90 per cent RH. Copyright © 2002 John Wiley & Sons, Ltd.